The Intervention of Oral Stimulation in Low-Birth-Weight Infants With Weak Sucking Reflexes: A Case Study - Yutantri, Savitri Kartika; Mamuroh, Lilis; Trisyani , Mira (Utami Publisher, 2026)
Low birth weight (LBW) is a major cause of neonatal morbidity and mortality, with a prevalence of 3.9% in Indonesia and 3.04% in West Java in 2024. This condition increases the risk of death on the first day of life. One of the effects of LBW is neurological immaturity, which can cause sucking and swallowing reflex disorders. If not treated immediately, this condition can hinder nutritional fulfillment and increase the risk of growth failure. Therefore, nursing interventions are needed to stimulate sucking and swallowing abilities early on. Oral stimulation is a non-pharmacological nursing intervention believed to improve sucking reflexes in LBW infants. This study aims to evaluate the effectiveness of oral stimulation in improving sucking reflexes and nutritional intake in LBW infants. A case study was conducted on male neonates with LBW who received 10–15 minutes of oral stimulation intervention three times before feeding. The results showed an increase in sucking reflex strength from weak to strong, as well as an increase in the amount of nutrition intake from 10 ml to 15 ml per feeding. Oral stimulation is effective in improving oral motor function in LBW infants. This intervention can be recommended as a nursing action to support successful breastfeeding in LBW infants.